Social Identity and the Loss of Individuality in Toni Morrison’s a Mercy - Gökçen KARA (Celal Öney, 2021)
A central theme of social philosophy is that man and society are interrelated. Humans are physiologically and psychologically adapted to live and interact with others in groups and in society. In other words, humans have both an individual identity and a social identity. Personal identity can change according to the perceptions and stimuli of the environment. In other words, it can be said that individual identity is influenced by social identity to adapt to the environment. In fact, social identity or group identity has a stronger influence than individual identity. A person may take some actions that do not fit his individual identity in order to be recognized in the society. There are significant interrelationships between individual identity and social identity. People who develop a collective identity as a member of a group can change and redefine their personality when they act in certain situations. Toni Morrison 's novel A Mercy (2008), which is the subject of this paper, deals with the conflict between individual identity and social identity and the social processes that influence individuals' decision making. The novel is also about the helplessness of the individual in the face of society. A Mercy uses the characters in the novel to illustrate the influence of society and social interactions, i.e. a dominant power over the individual, on the process of identity formation and how one is shaped by social forces.